2020
DOI: 10.24275/rmiq/bio1793
|View full text |Cite
|
Sign up to set email alerts
|

Dextran synthesis by native sugarcane microorganisms

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The results obtained in this research are similar to other reports that indicate that high concentrations of a carbon source can improve EPS production, particularly for levan [26,53]. Likewise, the results are consistent with the results obtained by Zhang et al [55], who reported a maximum EPS yield when 300 g/L of sucrose was used as a carbon source with Bacillus methylotrophicus.…”
Section: Effect Of Carbon Source On Exopolysaccharide Productionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results obtained in this research are similar to other reports that indicate that high concentrations of a carbon source can improve EPS production, particularly for levan [26,53]. Likewise, the results are consistent with the results obtained by Zhang et al [55], who reported a maximum EPS yield when 300 g/L of sucrose was used as a carbon source with Bacillus methylotrophicus.…”
Section: Effect Of Carbon Source On Exopolysaccharide Productionsupporting
confidence: 92%
“…The region in the range of 3000-2800 cm −1 indicates the stretching vibration of CH and confirms the presence of fructose [22]. The spectrum band at 1644 cm −1 indicates carbonyl stretching [43], and the peak at 1440 cm −1 The results obtained in this research are similar to other reports that indicate that high concentrations of a carbon source can improve EPS production, particularly for levan [26,53]. Likewise, the results are consistent with the results obtained by Zhang et al [55], who reported a maximum EPS yield when 300 g/L of sucrose was used as a carbon source with Bacillus methylotrophicus.…”
Section: Characterization Of Exopolysaccharides With Fourier-transfor...supporting
confidence: 88%
See 1 more Smart Citation
“…The reaction for the formation of dextran is catalyzed by dextransucrase the enzymes that is produced by Leuconostoc spp. The presence of dextran indicates the presence of microorganisms that cause sucrose inversion [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed the importance of the source of the LAB strains to unveil novel EPS structures that can have important technological and functional roles for food fermentation systems as well as food technology [8,9]. In terms of the fermentation environment, pickled vegetables might be important sources for homopolymeric EPS producer LAB strains as sucrose presents within this fermentation environment.…”
Section: Introductionmentioning
confidence: 99%